Real-financial linkages in the Canadian economy: An input-output approach - Danny Leung; Oana Secrieru (Bank of Canada, 2011)
The purpose of this paper is twofold. First, we provide a detailed social accounting matrix (SAM), which incorporates the income and financial flows into the standard input-output matrix, for the Canadian economy for 2004. Second, we use the SAM to assess the strength of the real-financial linkages by calculating and comparing real SAM multipliers and financial social accounting matrix (FSAM) multipliers. For FSAM multipliers, financial flows are endogenous, whereas for real SAM multipliers they are not. Our results show that taking into account financial flows increases the impact of a final demand shock on Canadian output. Financial flows also play an important role in determining the cumulative effect of an income shock or the availability of investment funds. Between 2008 and the first half of 2009, financial institutions shifted their investments towards government bonds, short-term paper, and foreign investments. This shift together with the fact that non-financial institutions were unwilling or unable to increase their financial liabilities, led to estimated declines in all GDP multipliers between 2008 and the first half of 2009 (2009H1). The main advantage of using the extended input-output impact analysis is that it provides a simple framework, with very few assumptions, which allows the assessment of the strength of real-financial linkages by means of multipliers. However, our methodology is subject to the Lucas critique, that as shocks shift prices, agents cannot adjust. Such a framework is, nevertheless, appropriate in short-term impact analysis such as ours.
Keywords: C67; D57; 330; Economic models; Financial markets; Sectoral balance sheet; Social Accounting Matrix; Input-Output; Finanzmarktkrise; Interindustrielle Verflechtung; Theorie; Kanada